Saúde bucal na infância: um modelo orientado para a gênese da saúde - Ana Pitchon (2021)
In the last decades of the 20th century and the beginning of the 21st century, the prevalence of dental caries showed a reduction in most developed countries. Despite this, caries remains the most frequent chronic disease in childhood, with an uneven distribution between countries and populations. The effort of the scientific community has focused, so far, on developing research focused on the etiopathogenesis and risk factors for the disease. Few studies have sought to analyze the positive factors, considered as active in health, that contribute to oral health in childhood. This theoretical essay aimed to propose a theoretical-conceptual model, incorporating the approaches of pathogenesis and salutogenesis, with guidance for the genesis of health. The methodology was structured through literature reviews that supported the elaboration of the model, based on factors that positively influence oral health in childhood, designated as healthy and protective factors, considered as active in health. These factors act at the level of the individual (child), family, community and environment, in an expanded concept of health, in which oral health cannot be dissociated from the child's general health. Therefore, to promote positive experiences in childhood, it is necessary to face social inequalities in health by providing better living conditions, access to quality public services and policies, necessary support for families and the development of effective strategies for health promotion and prevention.